IMPLEMENTATION OF HAJJ MANASIK PRACTICES IN IMPROVING THE UNDERSTANDING OF HAJJ WORSHIP AMONG STUDENTS OF MAS DARUL IKHLASH - Ali Jusri Pohan; Afrina Afrina; Aida Sahrani; Puja Puja; Cindy Aulia; Nur Azizah Lubis (LPPM Univ. Ibn Khaldun Bogor, 2026)
Hajj jurisprudence learning in madrasas is often theoretical, so students' understanding of the practice of the Hajj is not optimal. This study aims to describe the implementation of the Hajj ritual practice in improving the understanding of the Hajj ritual among students of grade XII MAS Darul Ikhlash, Dalin Lidang Village, Panyabungan District. This study uses a qualitative approach with a descriptive method. The research subjects included teacher Cindy, the subject of fiqh, and students of grade XII. Data collection techniques were carried out through observation of Hajj ritual practice activities, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Hajj ritual practice was carried out through direct simulation of the Hajj ritual series, including ihram, wukuf in Arafah, overnight in Muzdalifah, throwing the devil, tawaf, sa'i, and tahallul using a replica of the Kaaba and symbolic location markings. The implementation of this practice was able to improve the students' understanding of the cognitive aspects (understanding the order and laws of the Hajj), affective (appreciating spiritual values), and psychomotor (the ability to practice the Hajj rituals sequentially and correctly). Thus, learning based on Hajj ritual practices has proven effective in improving the understanding of the Hajj ritual among the students of class XII MAS Darul Ikhlash, Dalin Lidang Village, Panyabungan District.